2018
DOI: 10.1016/s2542-5196(18)30119-0
|View full text |Cite
|
Sign up to set email alerts
|

Availability, use of, and satisfaction with green space, and children's mental wellbeing at age 4 years in a multicultural, deprived, urban area: results from the Born in Bradford cohort study

Abstract: European Community's Seventh Framework Programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 30 publications
(30 reference statements)
2
83
1
4
Order By: Relevance
“…As expected, residents' levels of satisfaction with NGS and CGS are associated with better self-rated health outcomes. Such effects remain stable and robust after adjusting for socio-economic and neighbourhood characteristics, which is consistent with previous findings that satisfaction with green space could promote residents' health benefits [26]. This is plausible, since greater satisfaction with the environment would promote individuals' awareness to use and access urban green space and that potentially enhances people's health [40].…”
Section: The Effect Of Satisfaction With Neighbourhood Green Space (Nsupporting
confidence: 88%
See 2 more Smart Citations
“…As expected, residents' levels of satisfaction with NGS and CGS are associated with better self-rated health outcomes. Such effects remain stable and robust after adjusting for socio-economic and neighbourhood characteristics, which is consistent with previous findings that satisfaction with green space could promote residents' health benefits [26]. This is plausible, since greater satisfaction with the environment would promote individuals' awareness to use and access urban green space and that potentially enhances people's health [40].…”
Section: The Effect Of Satisfaction With Neighbourhood Green Space (Nsupporting
confidence: 88%
“…However, few studies have explored the association between satisfaction derived from the quality of green space and people's health outcomes. The importance of considering satisfaction arising from green space and people's mental health was demonstrated in a 4-year followed-up longitude cohort study in Bradford [26]. This study found that Asian children who are more satisfied with green space are also more significantly likely to have fewer behavioural difficulties, less internalizing behaviour, and greater positive behaviour within different buffers from the residence to green space.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…. Table 3 presents the results for studies looking at associations between ST (8 studies) or GT (5 studies) and psychological outcomes in young children [61][62][63][64][65][66][67][68][69][70][71][72][73]. Studies of young children comprised a total of 30,476 participants in ST studies (plus 483 families with unspecified numbers), 2,836 participants in GT studies, and 575 participants in studies exploring both ST and GT together.…”
Section: Young Children (<5 Years)mentioning
confidence: 99%
“…Analysis of BiB data has provided insights into the factors that affect health and wellbeing in pregnancy and early childhood, including on social and ethnic inequalities in health [14][15][16], the relationships between maternal gestational adiposity, gestational diabetes mellitus (GDM) and maternal circulating glucose concentrations and fetal growth, birth outcomes, infant and childhood health in South Asian and White European families [4,5,[17][18][19], the associations of environmental stressors such as green space and air pollution on health e.g. [20][21][22], exposures that may influence development of asthma and allergies [23] and the role of genetic variation in human health [12]. BiB data have underpinned more than 100 journal publications; a full list can be found at https://borninbradford.nhs.uk/.…”
Section: The Existing Bib Resourcementioning
confidence: 99%